TASAWUF DAN PLURALITAS DALAM Al-QUR'AN - Mawardi Mawardi (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2017)
This paper raises the issue of Sufism with the title "Sufism and Plurality in the Qur'an". Pluralism is derived from pluralist Latin, from pluris namely more than one, the plural. Therefore something said to be plural always consists of many things, various types, different points of view and background. Religious pluralism holds that no one is entitled to claim that religion is the most correct, all religions in this view have their own righteousness. The problem is that these pluralists always express the legitimacy of the Sufis, but the recognition of pluralism by the great Sufis may not exist in the Sufi tradition. From there, they assume that the idea of religious pluralism has indeed existed in the intellectual tradition of Islam and certainly based on Islamic teachings. The trend of harmonizing religions can be found from the two concepts that always reap the polemic and controversy that is the concept of unity of religions or better known in the world of tasawwuf with wahdat al-adyÄƒn and the concept of religious pluralism or better known in the world of philosophy with religious pluralism.So pluralism Religion is every religious person who is required not only to recognize the existence and rights of other schools, but to engage in understanding the similarities and differences in order to achieve harmony in diversity.